Financial market responses to a natural disaster: evidence from local credit networks and the Indian Ocean tsunami - Czura, Kristina; Klonner, Stefan (CESifo working papers, 2018)
Conventional wisdom in economics holds that traditional credit and insurance networks are inapt for insuring against covariate risks such as natural hazards. We challenge this claim by examining changes in financial allocations in Rotating Savings and Credit Associations (Roscas), a popular group-based financial institution world-wide, in the aftermath of the 2004 Indian Ocean tsunami. With financial data from locations along the South Indian coast that were affected by this natural disaster to different extents, we estimate the causal effect of this devastating economic shock on financial flows between occupational groups, the price of credit and other loan characteristics. We find that the supply of funds in these local credit networks remained remarkably stable, while demand by self-employed members increased significantly. In response, substantial funds were channeled from wage-employed members and commercial investors to small and medium-scale entrepreneurs. We conclude that traditional non-market financial institutions may be more important for coping with covariate risks in low-income environments than commonly assumed.
Keywords: Graue Literatur